2010
DOI: 10.1161/circep.110.957241
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Epicardial Adiposity and Atrial Fibrillation

Abstract: Background-Atrial fibrillation (AF) has been linked to inflammatory factors and obesity. Epicardial fat is a source of several inflammatory mediators related to the development of coronary artery disease. We hypothesized that periatrial fat may have a similar role in the development of AF. Methods and Results-Left atrium (LA) epicardial fat pad thickness was measured in consecutive cardiac CT angiograms performed for coronary artery disease or AF. Patients were grouped by AF burden: no (nϭ73), paroxysmal (nϭ60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(165 citation statements)
references
References 39 publications
6
153
2
4
Order By: Relevance
“…Al Chekakie et al (24) and Batal et al (25), referring to the association between pericardial fat volume and AF, suggested that the local effects of proinflammatory cytokines released from the pericardial adipose tissue may be a potential mechanism for the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Al Chekakie et al (24) and Batal et al (25), referring to the association between pericardial fat volume and AF, suggested that the local effects of proinflammatory cytokines released from the pericardial adipose tissue may be a potential mechanism for the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…8 They demonstrate a close association between peri-atrial EAT volume and the development of new-onset AF, independent of the presence of hypertension, diabetes, or LA enlargement, although a recent study demonstrated that, among several types of epicardial fat, only peri-atrial epicardial fat thickness at the esophagus was associated with AF burden independent of age, body mass index, or LA area. 9 Nakanishi et al have demonstrated for the first time that peri-atrial EAT volume predicted future AF events more accurately than total EAT volume during follow-up of 3.3±1.0 years. 8 These results suggest the potential role of peri-atrial EAT in the development of AF.…”
Section: Article P 2748mentioning
confidence: 97%
“…Our study targeted EAT surrounding the LA because the LA plays an important role in AF, particularly around the pulmonary veins. We identified sites of EAT anatomically, corresponding to five major LA GPs based on reports of the autonomic innervation of the heart [8,16,17]. In fact, EAT around the LA was found in these five major GP regions.…”
Section: Eat Around the Lamentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) is ectopic visceral fat that surrounds the heart, and increased EAT volumes correlate with the prevalence of AF, as well as with the recurrence of AF after ablation therapy [6,7]. Increased fat thickness at the posterior left atrium (LA) may be particularly related to the AF burden, independent of age, BMI, and the LA area [8,9]. Nevertheless, the mechanisms of AF pathogenesis and the formations of AF substrate due to EAT are not well understood.…”
Section: Introductionmentioning
confidence: 99%